E-MODULE INTERAKTIF BERBASIS FLIPBOOK PADA MATAKULIAH MACHINE LEARNING UNTUK MENINGKATKAN KREATIFITAS MAHASISWA - Nonik Erawati, Kadek; Dita Ardiani , Ni Nengah; Santiago, Gede Agus Santiago (Jurnal Penjaminan Mutu, 2024)
This flipbook-based interactive e-module aims to increase student creativity in the Machine Learning course. This module thoroughly explores basic concepts, algorithms, and practical applications in Machine Learning. The research method involved developing an engaging and interactive learning platform with features such as quizzes, video tutorials, and mini-projects. The research results show increased student engagement and understanding of Machine Learning concepts. This e-module can encourage creative approaches to solving problems. The conclusion highlights the importance of interactive e-modules in boosting creativity and practical learning in Machine Learning education, especially based on digital flipbooks; users can enjoy a more dynamic and interesting learning experience through images, graphs, and other visual elements. Using digital flipbooks, they can enjoy a more dynamic and engaging learning experience through the use of images, graphs, and other visual elements.